Disfungsi Kepemimpinan Kepala Sekolah dengan Rangkap Jabatan di Sekolah Pinggiran Kota - Al-Ghozali, Mohammad Faizal; Pabbajah, Mustaqim; Budiyono, Nararya Rahadyan; Yudhawati, Dian (Pencerah, 2024)
This study aims to identify dysfunctions experienced by school principals who hold additional roles in schools located in suburban areas, using a qualitative case study approach. Data were collected through observations and interviews with the principal and students to understand the impact of holding multiple positions on leadership and school management. The findings reveal that the principal faces significant challenges in time management, which affects the effectiveness of performing key tasks such as interacting with students and managing school administration. Contributing factors include a shortage of teaching staff and the assignment of additional roles to the principal that require more attention. Although the principal gains managerial experience from holding multiple positions, this negatively impacts optimal relationships with students and reduces overall leadership effectiveness. Based on the study’s findings, it is recommended to ensure a more equitable distribution of teaching staff, provide training in time management, and review policies regarding the limitation of holding multiple roles to enhance the quality of education in suburban schools.